Congenital Analbuminemia - Santosa, Putu Adi; Widijanti, Anik; Susianti, Hani; Intanwati, Sherly; Meilani, Rossy (MEDICINUS, 2020)
Congenital analbuminemia (CAA) is a rare autosomal recessive disorder, characterized by the absence or very low level of serum albumin (human serum albumin/HSA) as a result of defect on chromosome 4 which encodes albumin. It is defined as albumin level <1 g/l with normal liver function and the absence of protein loss.1,2 Estimated CAA prevalence is less than 1 in 1 million.A 10-year-old boy suffered from generalized edema that got worsened since last month. The patient had been misdiagnosed with nephrotic syndrome 2 years earlier, and then became protein-losing enteropathy. Neither cough nor diarrhea were reported. The patient had history of food allergy. Physical examination showed moderately ill condition, Glasgow Coma Scale (GCS) score E4 V5 M6, blood pressure 90/50 mmHg, pulse 120 x/min, respiratory rate 30x/min, palpebral edema, shifting dullness, undulation (+), with nonpitting edema on the extremities. Laboratory findings: leukocytosis (neutrophilia), peripheral blood smear showed hypochromic microcytic anisositosis erythrocyte. AAT serum 246 mg/dl, GGT serum: 88 U/l, iron serum 28 µg/dl, TIBC 411 µg/dl, transferrin saturation 7%, total IgE 775,90 U/ml. Serum Protein Electrophoresis (SPE) results were hypoalbuminemia (1,4 g/dl), hypogammaglobulinemia (0,21 g/dl), and total protein 2,91 g/dl. Chest X-ray showed pneumonia with minimal right pleural effusion. Overestimation of serum albumin level was caused by alpha and beta globulin that were detected as albumin in bromocresol green (BCG) methods. CAA aggravated with by allergy caused malnutrition in this patient. These data support the diagnosis of CAA with sepsis and iron deficiency anemia. Suggestion for the management consist of blood culture, procalcitonin level measurement, inguinal lymph node biopsy, DNA sequence analysis, also analysis of pleural and ascites fluid.